The All-American Canal Lining Project: interagency teamwork for conserving water - Peschel, Paul, author; Dahl, Wayne, author; Snipes, Paul, author; Kuzmich, Neena, author; Shields, Todd, author; Dull, Chris, author; Steele, Ken, author; Bradshaw, Vikki Dee, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
The All-American Canal Lining Project (AACLP) is one of the largest water conservation efforts in the United States saving 67,700 acre-feet of Colorado River water per year. This conserved water assists California in remaining within its Compact allocation of Colorado River Water without jeopardizing its agricultural or urban economies. It also contributes to the settlement of a long-standing San Luis Rey River water rights dispute in Southern California. Total project costs are projected to be over $300 million including design, construction, environmental mitigation, supervision, administration and litigation costs. The United States Bureau of Reclamation (Reclamation) completed construction of the unlined All-American Canal (AAC) in 1942. This 83-mile-long canal is operated and maintained by the Imperial Irrigation District (IID). As the largest irrigation district in the United States, with a total service territory encompassing nearly 1.1 million acres, IID supplies approximately 3.1 MAF of water per year to over 500,000 acres of highly productive agriculture farmland and nine communities. IID is the lead agency for the AACLP being responsible for project management, design, construction, and environmental compliance. Project funding is provided by the California Department of Water Resources (DWR) and the San Diego County Water Authority (SDCWA). As a result of this conservation, SDCWA will receive 56,200 acre-feet per year and the San Luis Rey Settlement Parties (SLRSP) 11,500 acre-feet. A Project Coordinating Committee (PCC) was established to provide project oversight, facilitate project decision making and provide a mechanism for structured communication among the participating entities and interested parties.
USCID water management conference
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.